(untitled) (New Delhi, 2002)
Introduction to austenitic stainless steels; Uniform corrosion of austenitic stainless steels; Pitting corrosion; Crevice corrosion; Sensitization and testing for intergranular corrosion; Metallurgical influences on stress corrosion cracking; Stress corrosion cracking of austenitic stainless steel weldments; Applications of fracture mechanics in stress corrosion cracking and introduction to life prediction approaches; Microbiologically influenced corrosion; Corrosion of austenitic stainless steel in liquid sodium; High temperature corrosion of austenitic stainless steel; Corrosion detection and monitoring in austenitic stainless steels using non-destructive testing and evaluation techniques; Corrosion related failures of austenitic stainless steel components; Surface modification for corrosion protection of austenitic stainless steels; General guidelines for corrosion control.
Keywords: materials science,strengh of materials,Khoa học vật liệu